EFEKTIVITAS HERBISIDA CAMPURAN b.a.: Pendimetalin 150 g/l + Metolaklor 300 g/l + Oksifluorfen 50 g/l UNTUK MENGENDALIKAN GULMA PADA BUDIDAYA BAWANG MERAH - Uum Umiyati; Denny Kurniadie; Deden Deden (Agroswagati Jurnal Agronomi, 2020)
The experiment was conducted with the aim the efficacy testing effectiveness of mixed herbicide with the active Pendimetalin 150 g/l + Metolaklor 300 g/l + Oksifluorfen 50 g/l in controlling Cyperus sp, Digitaria adscendens, Ageratum conyzoides, Portulaca virosa and other weeds in onion. The experiment was carried out in the field of Gebang Village, Babakan Subdistrict, Cirebon, Wast Java. Field experiment was started from Mei 2020 - July 2020. The design was used with randomized block design (RCBD) consist of eight treatments with four replications. The treatments tested were mixed herbicide at 1.0 l/ha, 1.5 l/ha, 2.0 l/ha, 2,50 l/ha, 3.0 l/ha, 3.5 l/ha, manual weeding and Untreated control (without herbicide). Result showed that mixed herbicide at 1.0 to 3.5 l/ha were effective to control Cyperus sp, Digitaria adscendens, Ageratum conyzoides, Portulaca virosa and other weeds in onion up to 6 WAA. mixed herbicide at the rate tested at 1.0 to 3.5 l/ha did not show crop safety issue to onion crops, no negative impact on number of tillers at vegetative stages, and it shown optimizing potential onion yield at 9,34 to 11,22 kg/plot.